Comparative Study of Serum levels of Granzyme H & Estrogen In Patients Suffering From Breast Cancer - Tahbaz lahafi, Behnoosh; Amirrassouli, Houshang; Akbari, Mohammad Esmaeil; Namaki, Saeed; Kazerouni, Faranak; Rahimipour, Ali; Mohammadzadeh, Jahangir (Archives of Advances in Biosciences, 2013)
GranymeH is a functional cytotoxic serine protease of NK cell granules,which expands the cell death-inducing repertoire of innate immune system.The purpose of this study was to determine GranymeH(GZMH)level in breast cancer(BC) and healty women.This study was performed on 30 patients with BC and 30 healty woman.GZMH and Estrogen levels were measured in cancer patients and healty women subsequently using ELISA and Radioimmunoassay(RIA) methods. Mean GZMH value was lower in BC than healty women(p<0.0001) and mean Estrogen level was higher in BC patients in comparison to healty women (p<0.003).Our finding indicates probability of existance of suppressor or a problem in production of GZMH in cancer patients